PROBLEMS OF CHILDHOOD AND EDUCATION IN CHARLES DICKENS’ WORKS - Student of CSPU The English language theory and practice department Tojiyeva Sevinch Anvar qizi Scientific advisor: Kenjayeva Muxlisa Baxodir qizi (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Rather than being isolated, English literature stands apart from the broader European tradition, boasting its own unique strengths and contributions. While it excels in various literary genres, some areas deserve particular recognition. Poetry, notoriously challenging to translate effectively, thrives within English literature, showcasing a richness and depth that places it amongst the world's best. Similarly, English humor, often difficult for non-native speakers to grasp, further distinguishes this literary tradition. Countering any claims of insularity, English literature boasts an impressive collection of travel writings, demonstrating a keen interest in exploring the world beyond its borders. Keywords: Oliver Twist, Dickens exposes, guise of education, world of literature, historical context, problems of childhood, Dickens’ legacy, schools for the poor.